Influence of Lactose Concentration in Bioethanol Production from Cheese Whey - Murari, Cleidiane Samara; Silva, Débora Cristina Moraes Niz da; Silva, Bruna Lima da; Bianchi, Vanildo Luiz Del (Acta Scientiarum. Technology, 2017)
The present study aimed the utilization of the cheese whey as substrate for ethanol production by Kluyveromyces marxianus.Â Was studied the effect of the initial concentration of cheese whey (M1 57,6 g L-1; M2 45,6 g L-1; M3 32,5 g L-1 e M4 18,8 g L-1) on the alcoholic fermentation. After sterilization, the medium were incubated at 30ÂºC for 48 hours, performing analysis of lactose, proteins, ethanol, cell growth and chemical oxygen demand. According to the results, the medium M1 (the highest concentration) showed a higher production and productivity of ethanol 16.9 g L-1 and 1.26 g L.h-1, respectively, and also obtained the highest production and productivity of cell of 5.8 g L-1 and 0.40 g L.h-1, respectively. However, in terms of ethanol yield, the most satisfactory result was obtained with the M3 medium with 82.30% in 12 hours of fermentation. The organic substances content has been reduced in relation to COD in the medium M4 in 82.28%, representing a promising alternative for valorization of cheese whey as an effective alternative to obtain a renewable source of biofuel.